Design and Testing of a Shell-Encapsulated Solar Collector with the Compound Surface Concentrators - Hongfei Zheng; Gang Wu; Jing Dai; Yanyan Ma (International Journal of Photoenergy)
This paper presents design and testing of a shell-encapsulated solar collector which can be used in north area of China for wall-amounting installation. The designed solar collector is based on the combination of a novel compound curved surface concentrator and an aluminum concentric solar receiver, which is contained in a glass evacuated-tube. As there is no perforative joint between the double-skin glass evacuated-tube and the aluminum concentric solar receiver, the difficulty of vacuum keeping for a glass-metal joint is avoided. The cavity shell provides an additional thermal insulation to reduce heat loss of the designed solar collector. The working principle of the compound curved surface concentrator is described. The ray-tracing results are given to show the effect of deviation angle of the concentrator on its optical efficiency, hence determining its maximum acceptance angle. A prototype of the designed solar collector has been constructed and tested under the sunny winter weather condition. The experimental results indicate that the hot water temperature higher than 80°C with a daily average efficiency of about 45~50% has been achieved at the average ambient temperature below 0°C, so the designed solar collector can produce hot water at a useful temperature in winter.